Collaboration of Colorado Cancer Genetic Counselors to Integrate Next Generation Sequencing Panels into Clinical Practice. Issue 4 (1st May 2014) - Wolfe Schneider, K.; Anguiano, A.; Axell, L.; Barth, C.; Crow, K.; Gilstrap, M.; Hamlington, B. A.; Lesh, S.; Mullineaux, L.; Rahm, A. Kulchak; Strait, E.; Freivogel, M.
Abstract: The recent introduction of clinically available next generation sequencing (NGS) cancer panels has presented new challenges for genetic counselors. Determining which patients are appropriate for NGS panel testing is complex. Due to the large number of genes included in the NGS panels, thorough and appropriate pre‐test counseling and interpretation of NGS results can be a time‐consuming and difficult process. Many of the genes associated with increased cancer risk lack published clinical management guidelines and estimates of cancer risk for individuals with deleterious mutations. In order to efficiently and effectively review the clinical utility of NGS panels, Colorado cancer genetic counselors formed a working group to gain a better understanding of the genes included in NGS cancer panels. This publication reports on the approach of this group, the process used to evaluate a selected NGS panel, future directions for this collaboration, and ideas for other genetic counselors to form similar groups to efficiently evaluate new technologies and improve practice.